(untitled) (Andamios, Revista de Investigación Social, 2013)
The following article deals with one of the most important explanations behind the lack of positive impact that social policy has in fighting inequality in Mexico and the Federal District in recent years. The article is based on an explanation that circles the famous debate in social policy over the impact that programs and projects have over inequality based on two of its most known methodologies: universalisation versus focalization of beneficiaries. Specifically, this article analises federal programs in México and programs implemented by the Federal District Government. The argument that it defends is that both programs designed by the Federal government and programs designed by the Federal District tend to universalize the reception of social benefits which in the end has no positive impact over inequality, but on the contrary, increase it by granting a larger percentage of social expenditure to high social classes. In this flaw, we find one of the main explanations behind the increases in inequality in Mexico in the last years despite the increase in social expenditure.